Design and Implementation of a Multiplier free FPGA based OFDM Transmitter (Journal of Engineering, 2013)
Orthogonal Frequency Division Multiplexing (OFDM) is an efficient multi-carrier technique.The core operation in the OFDM systems is the FFT/IFFT unit that requires a large amount of hardware resources and processing delay. The developments in implementation techniques likes Field Programmable Gate Array (FPGA) technologies have made OFDM a feasible option. The goal of this paper is to design and implement an OFDM transmitter based on Altera FPGA using Quartus software. The proposed transmitter is carried out to simplify the Fourier transform calculation by using decoder instead of multipliers. After programming ALTERA DE2 FPGA kit with implemented project, several practical tests have been done starting from monitoring all the results of the implemented blocks (VHDL code) and compare them with corresponding results from simulation system implemented in matlab 2010a. The results of these practical tests show that the suggested approach gives a significant improvement in reducing complexity and processing delays (45 nsec) in comparison with the conventional implementations of OFDM transmitter.